Potentially Inappropriate Psychotropic Drug Prescriptions and Polypharmacy among Geriatric Home Healthcare Patients: A Cross-Sectional Study - Kayahan, Selin Tanyeri; Kayahan, Ali (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction Comorbidities, psychotropic drug use and polypharmacy are common in elderly individuals. Research evaluating the psychotropic drug prescriptions among geriatric patients in a homecare health setting is limited. This study aimed to examine the medications of geriatric home healthcare patients regarding psychotropic drugs and polypharmacy and to assess their potential inappropriateness. Materials and Methods Sociodemographic, clinical, drug prescription and home health service-specific data of patients who were 65 or older and registered in a home healthcare unit were collected from the electronic files. Comorbidities were scored according to the Charlson Comorbidity Index and the safety of psychotropic drugs was evaluated with the 2023 version of the American Geriatric Society’s Beers Criteria. Results Of the 229 patients included, 69.9% (n=160) were women and the mean age was 83±7.97. 2 out of every 3 patients were considered severely ill. Polypharmacy was 78.6% (n=180) and at least 1 psychotropic drug was prescribed for half of the sample. The average of prescribed psychotropic drugs was 2.01±1.18 and potentially inappropriate psychotropic drug prescriptions were 46% (n=52). The most frequently prescribed antidepressants and antipsychotic were escitalopram (50.7%) and quetiapine (65.3%). Polypharmacy and psychotropic drug prescriptions were associated with age (OR: 0.93, 95% CI: 0.89-0.97, p=.004; OR:4.13, 95% CI:1.03-16.59, p=.045) while potentially inappropriate psychotropic drug prescriptions were associated with antipsychotic medication (OR:15.90, 95% CI:3.46-72.96, p<.001). Conclusion Potentially inappropriate psychotropic medication seems frequent among geriatric patients. Considering the aging population, it will be of great importance for clinicians and pharmacists to carefully evaluate psychotropic prescriptions and polypharmacy.
Keywords: Beer’s criteria; Clinical pharmacy; Geriatric cases; Home healthcare services; Polypharmacy; Psychotropic drugs